Exploring the relative contributions of learning motivations and test perceptions to autonomous English as a foreign language learning and achievement - Liu, Xiaohua; Dong, Manxia (Frontiers in Psychology, 2023)
Past studies on the contributions of language learning motivations and test perceptions to language learning have been conducted relatively independently, with few simultaneously gauging the relative effects of these two types of variables on learning behaviors and outcome. In contexts where testing plays a significant role in language education, it is argued that both types of variables are likely to influence language learning. Through a series of multiple regression analyses, this study juxtaposed the relative effects of three types of language learning motivation (i.e., integrative, development and requirement motivation) and two types of perception of a high-stakes English test on Chinese high school students’ (n = 3,105) EFL learning practice and achievement, casting fresh lights on the motivational factors of EFL learning practice. More specifically, it was found that integrative and development motivations were the major drives behind students’ overall effort expenditure on EFL learning for Year 1 students. For students from higher grades who were more closely confronted with the test, however, the effect of development motivation diminished and that of perceived test validity increased. The same pattern applied to students’ reported learning achievement. The motivational profiles behind each specific type of learning practice and their variational patterns across grades were also found to differ. Implications for both research and educational practice are discussed.